Potential of Red Okra Extract (Abelmoschus esculentus L. Moench) to Restore Kidney Damage due to Sodium Nitrite - Wahyuningsih, Sri Puji Astuti; Fachrisa, Amalia; Nisaâ€™, Nabilatun; Kusuma, Baskara Wiku Adi; Shoukat, Nadia; Ahmar, Rasyidah Fauzia; Alifiyah, Na'ilah Insani (Biosaintifika: Journal of Biology & Biology Education, 2021)
Sodium nitrite (NaNO2) found in vegetables, drinking water, and cured meats, can damage tissue because it is an oxidant. Plant phytochemicals such as quercetin are antioxidants. This study aimed to determine the potential of red okra pods ethanol extract (ROE) to repair kidney damage in mice (Mus musculus) induced by NaNO2. The red okra pods were extracted three times with saturated ethanol. The experiment used 36 male BALB/c mice aged 6-8 weeks and body weight of about 28 g. There are six research groups, namely, normal control, negative control (exposure to NaNO2 50 mg/kg BW), treatment of exposure to NaNO2 and administration of ROE at doses of 25, 50, 75, and 100 mg/kg BW. Sodium nitrite and ROE were given daily for 23 days by gavage. On day 24, the serum was isolated. Blood urea nitrogen (BUN) and creatinine (Cre) levels are measured to assess kidney function, as well as measuring the oxidant malondialdehyde (MDA) and the antioxidant enzyme of superoxide dismutase (SOD). The kidneys were made histological preparations and analyzed on the proximal convoluted tubule (PCT).Â  All data were statistically analyzed (Î±=0.05). This study indicated that the administration of ROE at a 100 mg/kg BW dose is the most optimal in repairing damage to the PCT with increased normal cells and reduced necrosis. Besides, it degraded BUN, Cre, and MDA levels in the serum of mice exposed to NaNO2 compared to the other treatments. All doses of ROE promoted the SOD level. ROE restore kidney tissue, especially on PCT to normal. Kidney damage due to exposure to NaNO2 preservatives can be reduced by administering ROE. ROE prevents kidney damage through an increase in antioxidant enzymes. ROE can be used as a food ingredient as a source of antioxidants, thereby reducing the impact of oxidant compounds.